2017
DOI: 10.1007/s11745-017-4306-6
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Uptake Mechanisms Involved in the Clearance of Non‐Protein Nanoparticles that Mimic LDL Composition: A Study with Knockout and Transgenic Mice

Abstract: Lipid core nanoparticles (LDE) resembling LDL behave similarly to native LDL when injected in animals or subjects. In contact with plasma, LDE acquires apolipoproteins (apo) E, A-I and C and bind to LDL receptors. LDE can be used to explore LDL metabolism or as a vehicle of drugs directed against tumoral or atherosclerotic sites. The aim was to investigate in knockout (KO) and transgenic mice the plasma clearance and tissue uptake of LDE labeled with H-cholesteryl ether. LDE clearance was lower in LDLR KO and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…In this regard, it had been also showed that in athletes the removal of LDE from the circulation was vefold greater than in sedentary (Vinagre et al 2007). Experiments with LDL KO mice submitted to training showed that LDL receptor overexpression also occurred, which can account for the higher LDE removal (Daminelli et al 2017). In this setting, the present study has two primary objectives: to test the antitumoral action of the taxane LDE-docetaxel in an animal model of prostate cancer and, secondly, to verify whether physical exercise increases the antitumoral action of LDE-docetaxel.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, it had been also showed that in athletes the removal of LDE from the circulation was vefold greater than in sedentary (Vinagre et al 2007). Experiments with LDL KO mice submitted to training showed that LDL receptor overexpression also occurred, which can account for the higher LDE removal (Daminelli et al 2017). In this setting, the present study has two primary objectives: to test the antitumoral action of the taxane LDE-docetaxel in an animal model of prostate cancer and, secondly, to verify whether physical exercise increases the antitumoral action of LDE-docetaxel.…”
Section: Introductionmentioning
confidence: 99%